Plasma magnesium and the risk of new-onset hyperuricaemia in hypertensive patients. Issue 2 (26th March 2020) - Cao, Jingjing; Zhang, Jingping; Zhang, Yuanyuan; Li, Huan; Jiang, Chongfei; Lin, Tengfei; Zhou, Ziyi; Song, Yun; Liu, Chengzhang; Liu, Lishun; Wang, Binyan; Li, Jianping; et al.
Abstract: We aimed to evaluate the relationship of plasma Mg with the risk of new-onset hyperuricaemia and examine any possible effect modifiers in hypertensive patients. This is a post hoc analysis of the Uric acid (UA) Sub-study of the China Stroke Primary Prevention Trial (CSPPT). A total of 1685 participants were included in the present study. The main outcome was new-onset hyperuricaemia defined as a UA concentration ≥417 μmol/l in men or ≥357 μmol/l in women. The secondary outcome was a change in UA concentration defined as UA at the exit visit minus that at baseline. During a median follow-up duration of 4·3 years, new-onset hyperuricaemia occurred in 290 (17·2 %) participants. There was a significantly inverse relation of plasma Mg with the risk of new-onset hyperuricaemia (per sd increment; OR 0·85; 95 % CI 0·74, 0·99) and change in UA levels (per sd increment; β −3·96 μmol/l; 95 % CI −7·14, −0·79). Consistently, when plasma Mg was analysed as tertiles, a significantly lower risk of new-onset hyperuricaemia (OR 0·67; 95 % CI 0·48, 0·95) and less increase in UA levels ( β −8·35 μmol/l; 95 % CI −16·12, −0·58) were found among participants in tertile 3 (≥885·5 μmol/l) compared with those in tertile 1 (<818·9 μmol/l). Similar trends were found in males and females. Higher plasma Mg levels were associated with a decreased risk of new-onset hyperuricaemia in hypertensive adults.